2002
DOI: 10.1186/1471-2490-2-7
|View full text |Cite
|
Sign up to set email alerts
|

A study of cytokeratin 20 immunostaining in the urothelium of neuropathic bladder of patients with spinal cord injury

Abstract: BackgroundNormal urothelium is characterised by terminally differentiated superficial cells, which express cytokeratin 20 in the cytoplasm. In contrast, cultured human stratified urothelium, which does not undergo complete terminal differentiation of its superficial cells, does not express cytokeratin 20. If spinal cord injury (SCI) affects urothelial differentiation or induces squamous or other metaplastic change undetected by histological analysis, the superficial urothelial cells of the neuropathic bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…These alterations are prevented by pretreatment with ganglionic blockers, suggesting that bladder nerves play a role in acute response of urothelial cells to injury. In SCI patients there is evidence that impairment of voluntary voiding may correlate with increased metaplasia and/or diminished urothelial differentiation (286). Changes in epithelial proliferation or metaplasia may be due to altered expression of molecules such as parathyroid hormone-related protein (PTHrP), which is a secretory factor that can act in autocrine, paracrine, as well as intracrine manners in a number of tissues.…”
Section: Neurogenic Injurymentioning
confidence: 99%
“…These alterations are prevented by pretreatment with ganglionic blockers, suggesting that bladder nerves play a role in acute response of urothelial cells to injury. In SCI patients there is evidence that impairment of voluntary voiding may correlate with increased metaplasia and/or diminished urothelial differentiation (286). Changes in epithelial proliferation or metaplasia may be due to altered expression of molecules such as parathyroid hormone-related protein (PTHrP), which is a secretory factor that can act in autocrine, paracrine, as well as intracrine manners in a number of tissues.…”
Section: Neurogenic Injurymentioning
confidence: 99%
“…CK14 does not stain on normal urothelium and signifies vulnerability of the bladder to future disease. [29][30][31] It is detected in pathologic bladders, denoting squamoid phenotype change of urothelium. It is observed before morphologic squamoid differentiation and is considered a reactive response to urothelial stress or injury.…”
Section: Discussionmentioning
confidence: 99%
“…CK7, CK18, and CK19 are the markers expressed throughout all layers in normal urothelium [7] . Available literature towards urothelium basal layer characterization have shown that urothelium cells were expressing phenotypic marker CK5 and CK17, but they did not express phenotypic marker CK20, which is generally associated with differentiated superficial cells [7,8,9] . The urothelium or transitional epithelium of the urinary tract shows alterations in the expression and configuration of cytokeratin isotypes associated with stratification and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, such adult stem cells in human urothelium, displaying clonogenicity, self-renewal, and differentiation potential have not been elaborately described. Urothelial stem cells capable of regenerative potential were isolated from mice tissue, which was found to express sonic hedgehog and p63 proteins in the basal cell layers of the bladder urothelium [7,8] . A recent report has also shown p63 expression in porcine urothelial and human urothelial cells [9] .…”
Section: Introductionmentioning
confidence: 99%